Rekomendasi Pemupukan N, P dan K pada Tanaman Padi Sawah (Oryza sativa L.) dalam Program Operasi Pangan Riau Makmur (OPRM) di Kabupaten Kampar - Ardiansyah, Ruli Febri (Jurnal Agro Teknologi Tropika, 2014)
An experiment to study the growth and yield components the efficiency of N, P and K fertilizers for paddy rice in theprogram of prosperous Riau food operation (OPRM) and to define the exactly recommended fertilizer in Kampar district hasbeen conducted from July to November 2011. The research was conducted using Randomized Block Design (RBD) with 6treatments and 4 replications. The further test has been conducted using DNMRT 5 %. The treatments consisted of : A0=withoutfertilizer; A1=7.5 g Urea, 6 g TSP and 3 g KCl per plot; A2=15 g Urea, 12 g TSP and 9 g KCl per plot; A3=22.5 g Urea, 18 gTSP and 15 g KCl per plot (dosage of fertilizers recommended in the program of prosperous Riau food operation in Kampardistrict); A4=30 g Urea, 24 g TSP and 21 g KCl per plot; and A5=45 g Urea, 30 g TSP and 15 g KCl/plot (dosage of fertilizersrecommended in the program of prosperous Riau food operation in Riau). The results showed that effect of N, P and K fertilizersfor paddy rice was significant in increasing the number of productive tillers, the percentage of grain filled and grain yield,whereas the parameters of 100-grains weight, and the efficiency of grains was not significant. The application of N, P and Kfertilizers 45 g Urea, 30 g TSP, and 15 g KCl per plot (150 kg.ha-1 Urea, 100 kg.ha-1 TSP, and 50 kg.ha-1 KCl) which was thedosage of fertilizers recommended in the program of prosperous Riau food operation at Riau increased grain yield better thanthe other dosage. If converted to hectar, the yield was equals to 4,07 tons.ha-1.Whereas, the highest of grain yield efficiency wasat dosage of 7.5 g Urea, 6 g TSP and 3 g KCl per plot (25 kg.ha-1 Urea, 20 kg.ha-1 TSP and 10 kg.ha-1 KCl). The recomendeduse of fertilizers for paddy rice planted with PB-42 variety in Kampar District was suggested at a dosage of 150 kg.ha-1 Urea,100 kg.ha-1 TSP and 50 kg.ha-1 KCl.Keyword: recommendation, N, P, K fertilizers, paddy- rice, efficiency, OPRM program